Japanese Occupation Government Policy in Indonesia on Culture and Literature: A Case Study of Asia Raja Newspaper (1942-1945) - Maman S Mahayana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
There are three views are shown in the movement of Indonesia in responding to the arrival of Japan to Indonesia. First, they welcome and support the arrival of Japan considering the success of Japan drove the Dutch. Second, they have not determined the attitude of supporting or opposing. In this case, they still want to see how Japan would run his administration in Indonesia. Third, they oppose the presence of Japan, although not yet dared to take the fight. Those who oppose the Japanese arrivals in Indonesia consists of two groups, namely (1) of the aristocratic, ambtenaar, and government employees, and (2) the movement of the fighters who put the government of Japan as an imperialist occupation. How is the real politics of the Japanese occupation government in carrying out its colonial administration in the colonies? With the underlying research on the Asia Raja newspapers (April 29, 1942 to September 7, 1945), this paper tries to reveal the political government of Japan in the socio-cultural and literature. How is the newspapers used the Japanese occupation government to gain public support for Indonesia in the face of Greater East Asia war?